A dimensional framework for the use of ASPD in SVP civil commitment - Rokop, James (The journal of forensic psychiatry & psychology, 2021)
The U.S. Supreme Court indicated in Kansas v. Crane that a qualifying mental disorder for Sexually Violent Predator civil commitment must differentiate between the ‘dangerous sexual offender’ and the ‘ordinary criminal recidivist,’ an issue of particular relevance when Antisocial Personality Disorder is the diagnosed condition. The DSM-5 categorical framework can be problematic in forensic contexts where the legal definition calls for a complex, layered, and nuanced approach. Dimensional schemes describe personality pathology in a flexible, individualized, and in-depth manner. In this paper we propose the expansion of DSM-5 ASPD criteria through the Alternative Model for Personality Disorders as a dimensional bridge to the SVP legal definition of a mental disorder. To that end, we first explain why a dimensional framework is plausible for the SVP definition of a mental disorder. Next, we review dimensional elements of ASPD impairments that serve to differentiate the sexually dangerous person from the ordinary criminal recidivist. Lastly, we provide a practical model that a forensic evaluator can use to determine whether to accept or reject ASPD as a viable SVP mental disorder.